Kajetan Kraszewski a kwestia unicka na Podlasiu w świetle Silva rerum. Wybrane problemy - Czyżewski , Feliks (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article presents Kajetan Kraszewski’s opinions on the Uniate Church in Podlasie, included in his Silva rerum. The views of the author of Kronika rodzinna (Family chronicle) are confronted with the statements of the researchers (mostly historians, literary scholars and linguists) within the broad context of the political, social and cultural life of the Polish-Lithuanian Commonwealth and the partition periods. By comparing research literature and excerpts from Silva rerum, the article analyses the effects of the Union of Lublin and the Union of Brest for the peasant community of Podlasie in the 1860s and 1870s. As presented in Kajetan Kraszewski’s Kronika, the tragedy of the followers of the Uniate Church in Podlasie resulted from the social and religious conditions that fuelled the divides during the time of the Russian partition (divide et impera). Kraszewski’s Silva rerum constitutes an image of the distance with which peasants treated Podlasie’s Uniate Church members, similar to the latter’s during the “masters’” uprising of 1863 (“in the masters’ uprising – we stayed aside watching”).